2018
DOI: 10.24017/science.2018.2.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Growth Traits and Yields Components of five Chickpeas Genotypes (Cicer arietinum L.) at Bakrajo/ Sulaymaniyah Conditions

Abstract: This study was carried out in Bakrajo Technical Institute, affiliates to the Sulaimania Polytechnic University. The investigation was done to find the relationships between genotypes and sowing times of five chickpeas (Cicer arietinum L.) during 2017-2018 seasons. Genotypes and sowing time are two significant variables which have impact on crop performance. However, heat stress throughout reproductive growth it is possible to cause Significant productivity loss. According to the environment conditions in winte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The production of local variety of chickpea in Kurdistan region is limited due to its low yield amount as investigated by many researchers in the region. According to study which was done by [8] the second lowest yield of chickpea was observed in the plot that the local variety seeds were used as compared to the other variety such us Ghab1, Filip1 and Filip 2. In a study which was done by Sulaimany chamber of commerce and industry it has revealed that one of the largest cereal importer company imports 70% of their cereal products from other countries while, only 30% is locally cultivated and chickpea is one of the crops that imported from other countries [9].…”
Section: Introductionmentioning
confidence: 99%
“…The production of local variety of chickpea in Kurdistan region is limited due to its low yield amount as investigated by many researchers in the region. According to study which was done by [8] the second lowest yield of chickpea was observed in the plot that the local variety seeds were used as compared to the other variety such us Ghab1, Filip1 and Filip 2. In a study which was done by Sulaimany chamber of commerce and industry it has revealed that one of the largest cereal importer company imports 70% of their cereal products from other countries while, only 30% is locally cultivated and chickpea is one of the crops that imported from other countries [9].…”
Section: Introductionmentioning
confidence: 99%